Effect of transport length and genotype on tonic immobility, blood parameters and carcass contamination of free-range reared chickens. Issue 3 (3rd July 2018) - Cartoni Mancinelli, Alice; Mugnai, Cecilia; Castellini, Cesare; Mattioli, Simona; Moscati, Livia; Piottoli, Luca; Guarino Amato, Monica; Doretti, Marco; Dal Bosco, Alessandro; Cordovani, Elisa; Abbate, Ylenia; Ranucci, David
Abstract: The aim of the present study was to investigate the effect of transport on welfare traits, several haematological parameters and carcase hygiene in two different chicken genotypes (fast- and slow-growing strains) reared under free-range conditions. For this aim, two hundred male chicks, 100 from fast-growing (Ross 308, R) and 100 from slow-growing (Naked Neck, NN) strain were farmed. At the end of the rearing period, at 81 days of age, 56 birds/strain were randomly selected for slaughtering and submitted to two different pre-slaughter conditions: no transport (0h) or 4 hours of transport (4h). Tonic immobility (TI), blood parameters and carcase hygiene traits were determined. Strain and transport significantly affected TI of birds. Both experimental factors and their interaction significantly affected plasma creatine kinase, alkaline phosphatase, alanine aminotransferase and aspartate aminotransferase. Cholesterol and triglycerides were not different between the experimental groups, whereas glucose decreased after 4 hours of transport in both strains. A significant difference between groups for the heterophils/lymphocytes ratio after transport was also observed, with NN being higher than Ross. Concerning the oxidative stress, we observed a higher ROS production in NN chickens. The carcase microbial characteristics showed a higher level of contamination after the transport (total viable counts), but not concerning the Enterobacteriaceae counts.